Low-temperature growth of diamond films using supersonic DC arcjet - Romanyuk, A.; Gottler, H.; Popov, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Diamond film growth on silicon at substrate temperature between 180 to 360 oC has been studied. The influence of hydrocarbon source on growth conditions and on diamond quality has been also investigated. Several series of experiments were performed to investigate the influence of substrate temperature on the diamond growth rate and the diamond quality. The quality of the deposited diamond films was controlled with Raman spectroscopy. It was shown that using methane as hydrocarbon source the growth rate up to 1.5 μm/h can be achieved. The use of ethane leads to the lower growth rate, but the quality of diamond film, crystallite morphology are better. Decrease of the substrate temperature down to 180°C leads to smaller grain size as well as to decreasing of diamond impact in the film.